MY NAME IS TYSON: IDENTIFYING PROPER NAME TRANSLATION AND ITS EFFECT(S) IN BEYBLADE - Silvy Cinthia Adelia; Shun Hirano; Yeni Yulia Andriani; Ephrilia Noor Fitriana; Dwi NCS Kusumaningtyas (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2023)
This study examines the procedures adapted for the proper translation of (character) names in the anime Beyblade and the effects of applying these translation procedures. Character names belong to the Culture Specific Items (CSIs) group known as proper names. As a CSI, names can contain historical and/or cultural references, which makes them difficult to translate. The study extracted the original names from the source text, Bakuten Shoot Beyblade, and compared them to their English version in the target text, Beyblade. The data collected were analyzed using the translation procedures proposed by Fernandes (2006) and Hervey Higgins (1992) to determine how the translation affects the movie. The analysis indicated that name translation in Beyblade mainly employed translation procedures of Recreation, Substitution, and Copy. They result in the loss of cultural reference and hidden meaning behind the names, affecting the story's intrinsic elements, particularly regarding the plot and characterization. The American audiences, therefore, are deprived of the opportunity to gain specific insights into the characters’ roles, relationships, and traits embedded in the character names of the original Bakuten Shoot Beyblade.